TBT toxicity and bioremediation in soils: bioassays with invertebrates - Silva, Patrícia Maria Veríssimo de Pinho e (2012)
Tributyltin (TBT) compounds were broadly used as ingredient of antifouling paints for ships. Among other effects, TBT is known to be associated with endocrine disruption. In 2008, the International Maritime Organization – IMO banned globally the use of TBT-based coatings, but due to their persistence and widespread use during the last 50 years, TBT became a ubiquitous compound in the environment. TBT reaches soil through various sources and constitutes a risk for soil fauna, namely the invertebrates, and consequently to soil function. However, soil contamination by TBT and its inherent effects have received very little attention. Nowadays, biological degradation is considered to be the major pathway for TBT removal from the environment. As example, Aeromonas molluscorum Av27 is a bacterium that degrades TBT into DBT (dibutyltin) and MBT (monobutyltin) in aqueous solution and therefore has the potential to be used to develop a biosensor to detect TBT in soils and sediments and to bioremediate this pollutant. This work was conducted considering the following goals: a) assess the toxicity of TBT on the invertebrates Porcellionides pruinosus and Folsomia candida; b) use bioassays with P. pruinosus and Micrococcus luteus to evaluate the potencial of TBT degradation in soil by the bacterium Aeromonas molluscorum Av27. For TBT toxicity evaluation, the isopod P. pruinosus was exposed to TBT contaminated food and soil and the exposure effects were assessed through feeding inhibition tests. An avoidance behaviour test was also carried out with this species. The collembolan F. candida was exposed to TBT contaminated soil and its reproduction success was evaluated. Soil bioremediation by A. molluscorum Av27 was assessed through bioassays using the bacterium M. luteus as indicator strain and a feeding inhibition test with P. pruinosus. The experiment took into account all components of exposure and was divided into three simultaneous sub-experiments: TBT-feeding test, with soil contaminated with TBT; TBT-growth media test, with soil contaminated with TBT in TSB growth medium; TBT-Av27 test, soil contaminated with TBT and inoculated with A. molluscorum Av27 in TSB medium. Regarding the toxicity bioassays, the results of the isopod exposure indicate a dose related response between the decrease of feeding parameters (consumption, assimilation and egestion ratios) and toxicant exposure. Results of the avoidance behaviour test showed that this species is able to detect very low concentrations of TBT and escape from the contaminated soil. The number of juveniles springtails and adult collembolan survival also showed a decrease with the increase of TBT concentration. F. candida revealed to be more sensitive to TBT than P. pruinosus, showing lower EC50 and LC50 values. Regarding bioremediation tests, the bioassay with M. luteus revealed that soils inoculated with A. molluscorum Av27 are less toxic to this organism, suggesting a decrease on TBT toxicity due to its degradation or its availability in the medium. From the bioassay with isopods, the TBT-growth medium test presented the highest toxicity of the three tests and its comparison with TBT-Av27 test may indicate TBT degradation by Av27. Besides the lower EC50 value of TBT-Av27 than the one obtained for TBT-feeding, it showed higher consumption ratios. In conclusion, the tested organisms revealed to be sensitive to TBT contamination in soil, at the concentration ranges used, since TBT showed to affect the behaviour and feeding performance of isopods and the reproduction success of collembolan. Bioremediation results need to be confirmed by chemical analyses of soils to show that TBT was really degraded to DBT and MBT, although results obtained so far are suggestive that A. mollucorum Av27 is able to bioremediate TBT contaminated soils. Furthermore, feeding inhibition bioassay with P. pruinosus and inhibition growth bioassay with M. luteus are likely to be viable tools to assess toxicity from TBT bioremediated soils, although the culture medium used to grow the bacterium has changed the toxicity of the chemical compound. Therefore, adaptations to the methodologies may be needed and new studies should be performed as well.